The Influence of Demonstration Learning Method on Student Learning Outcomes in the Subject of Archiving - Fajar Srimulana; Muh Darwis; Sitti Hardiyanti Arhas (ASHA Publishing, 2025)
Learning outcomes reflect students’ understanding, skills, and knowledge gained through various educational experiences, often demonstrated through academic achievements such as examination scores or awards. This study investigates the influence of the demonstration learning method on student learning outcomes in the Archiving subject for Grade XI students of the Office Management and Business Services (MPLB) program at SMK Negeri 1 Sinjai. A quantitative research approach was employed, with data collected through documentation, observation, and questionnaires. The data were analyzed using both descriptive and inferential statistical techniques. The findings reveal that the demonstration method, as determined and applied by educators, has an influence on students’ learning outcomes in the archiving subject. However, the correlation coefficient test indicates a low relationship between the use of the demonstration method and student achievement. Furthermore, the coefficient of determination shows that the demonstration method accounts for only 6% of the variance in learning outcomes, assuming other influencing factors remain constant. These results suggest that while the demonstration method plays a role in supporting student learning, its impact is limited and may require integration with other instructional strategies to enhance effectiveness. The study highlights the need for educators to consider a variety of methods to optimize student engagement and achievement in vocational education settings.